2013
DOI: 10.4103/1742-6413.112648
|View full text |Cite
|
Sign up to set email alerts
|

Performance of endoscopic ultrasound-guided fine needle aspiration in diagnosing pancreatic neuroendocrine tumors

Abstract: Background:Pancreatic neuroendocrine tumors (PNETs) are rare tumors of the pancreas, which are increasingly diagnosed by endoscopic ultrasound-guided fine needle aspiration (EUS-FNA). In this retrospective study, we assessed the performance of EUS-FNA in diagnosing PNETs.Materials and Methods:We identified 48 cases of surgically resected PNETs in which pre-operative EUS-FNA was performed. The clinical features, cytological diagnoses, and surgical follow-up were retrospectively reviewed. The diagnostic performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Previous studies have reported a EUS-FNA sensitivity between 80% and 90% [6,[11][12][13].The cytological yield in our series improved from 59% between 2003 and 2007 to 80.7% between 2008 and 2011. The improvement in our figures is possibly due a combination of the following factors: increased awareness among endosonographers and cytopathologists, use of LBC for processing and increasing the number of categorical diagnosis by reducing the number of samples categorised as atypical or suspicious [21][22][23].…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have reported a EUS-FNA sensitivity between 80% and 90% [6,[11][12][13].The cytological yield in our series improved from 59% between 2003 and 2007 to 80.7% between 2008 and 2011. The improvement in our figures is possibly due a combination of the following factors: increased awareness among endosonographers and cytopathologists, use of LBC for processing and increasing the number of categorical diagnosis by reducing the number of samples categorised as atypical or suspicious [21][22][23].…”
Section: Discussionmentioning
confidence: 87%
“…In addition, both tumors may form true rosettes or pseudorosettes . In contrast, the classic salt‐and‐pepper chromatin pattern of pancreatic neuroendocrine tumor is not a common feature of olfactory neuroblastoma, whereas neurofibrillary matrix has not been observed in the former . Well‐differentiated pancreatic neuroendocrine neoplasms may stain positively for synaptophysin, chromogranin A (Figure E), and CD56 (Figure C) .…”
Section: Discussionmentioning
confidence: 98%
“…The differential diagnosis should include well‐differentiated pancreatic neuroendocrine tumors. Similar to olfactory neuroblastoma, they may appear as a monomorphic population of dispersed or loosely cohesive tumor cells with scant cytoplasm . In addition, both tumors may form true rosettes or pseudorosettes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples can be taken using a variety of image-guided techniques, including endoscopic retrograde cholangiopancreatography, transabdominal ultrasound (US) and computed tomography (CT) [11,12]. However, endoscopic US-guided FNA (EUS-FNA) is the modality most commonly employed today to sample pancreatic lesions and has the potential to make a diagnosis in lesions as small as 5 mm in the pancreatic head and body with a sensitivity greater than 85% [12,13]. Overall, the sensitivity of EUS-FNA ranges between 80 and 90%, with specificity approaching 100% [13,14].…”
Section: Introductionmentioning
confidence: 99%